Promotion of human mesenchymal stem cell osteogenesis by PI3-kinase/Akt signaling, and the influence of caveolin-1/cholesterol homeostasis. Issue 1 (December 2015) - Baker, Natasha; Sohn, Jihee; Tuan, Rocky
Abstract Introduction Stem cells are considered an important resource for tissue repair and regeneration. Their utilization in regenerative medicine will be aided by mechanistic insight into their responsiveness to external stimuli. It is likely that, similar to all other cells, an initial determinant of stem cell responsiveness to external stimuli is the organization of signaling molecules in cell membrane rafts. The clustering of signaling molecules in these cholesterol-rich membrane microdomains can affect the activity, specificity, cross-talk and amplification of cell signaling. Membrane rafts fall into two broad categories, non-caveolar and caveolar, based on the absence or presence, respectively, of caveolin scaffolding proteins. We have recently demonstrated that caveolin-1 (Cav-1) expression increases during, and knockdown of Cav-1 expression enhances, osteogenic differentiation of human bone marrow derived mesenchymal stem cells (MSCs). The increase in Cav-1 expression observed during osteogenesis is likely a negative feedback mechanism. We hypothesize that focal adhesion signaling pathways such as PI3K/Akt signaling may be negatively regulated by Cav-1 during human MSC osteogenesis. Methods Human bone marrow MSCs were isolated from femoral heads obtained after total hip arthroplasty. MSCs were incubated in standard growth medium alone or induced to osteogenically differentiate by the addition of supplements (β-glycerophosphate, ascorbic acid, dexamethasone, and 1, 25-dihydroxyvitamin D3 ). The activation of and requirement for PI3K/Akt signaling in MSC osteogenesis were assessed by immunoblotting for phosphorylated Akt, and treatment with the PI3K inhibitor LY294002 and Akt siRNA, respectively. The influences of Cav-1 and cholesterol membrane rafts on PI3K/Akt signaling were investigated by treatment with Cav-1 siRNA, methyl-β-cyclodextrin, or cholesterol oxidase, followed by cellular sub-fractionation and/or immunoblotting for phosphorylated Akt. Results LY294002 and Akt siRNA inhibited MSC osteogenesis. Methyl-β-cyclodextrin, which disrupts all membrane rafts, inhibited osteogenesis. Conversely, Cav-1 siRNA and cholesterol oxidase, which displaces Cav-1 from caveolae, enhanced Akt signaling induced by osteogenic supplements. In control cells, phosphorylated Akt began to accumulate in caveolae after 10 days of osteogenic differentiation. Conclusions PI3K/Akt signaling is a key pathway required for human MSC osteogenesis, and it is likely that localization of active Akt in non-caveolar and caveolar membrane rafts positively and negatively contributes to osteogenesis, respectively.